2017
DOI: 10.4103/ua.ua_95_16
|View full text |Cite
|
Sign up to set email alerts
|

Management of renal caliceal diverticular stones: A decade of experience

Abstract: Objective:The objective of this study is to evaluate our methods for management of renal caliceal diverticular stones (CDS).Materials and Methods:We conducted a retrospective study from January 2005 to July 2015 and included patients who were treated for renal CDS. Patients were evaluated for treatment modality, puncture site (in case percutaneous nephrolithotomy [PCNL] attempted), operative time, stone clearance rate, and complications. During PCNL, if the infundibulum was found to connect the diverticulum to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In our study, the bull's eye technique has proved superior in such scenarios with better access, stone clearance rate, and a lesser number of punctures. In a study on management of calyceal stones by Patodia et al, they concluded that stone-guided puncture without dilation or creation of neo-infundibulum reduced operative time and morbidity with higher stone-free rate [ 7 ]. As compared to the supine, the prone position has a significantly shorter nephrostomy tract length and more potential access sites that provides ease and safety of percutaneous renal access [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the bull's eye technique has proved superior in such scenarios with better access, stone clearance rate, and a lesser number of punctures. In a study on management of calyceal stones by Patodia et al, they concluded that stone-guided puncture without dilation or creation of neo-infundibulum reduced operative time and morbidity with higher stone-free rate [ 7 ]. As compared to the supine, the prone position has a significantly shorter nephrostomy tract length and more potential access sites that provides ease and safety of percutaneous renal access [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, PCNL is preferred for such stones to achieve a stone-free status, particularly for a large diverticulum with a large stone burden [4]. Although, PCNL is more invasive than ureteroscopy (URS), it has the highest stone -and symptomfree rates (>90%) [5]. The reported incidence rates of infectious complications following PCNL are as follows: bacteremia 23%; endotoxemia 34%; fever 25%; and septic shock 0.3 to 2.5% [4].…”
Section: Discussionmentioning
confidence: 99%